Pegmatites of the Mokromoskovsk granite pluton - Lytvynenko, Yuliia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. The Mokromoskovsky pluton is composed of light gray granites and dark gray granodiorites. Light gray granites are composed of oligoclase (35-40%), microcline (20-25%), quartz (30-35%), and biotite (2-5%). Dark gray granodiorites contain oligoclase (40-55%), microcline (18-20%), quartz (25%), and biotite (5-7%). Light gray granites are microclinized in some areas and have acquired a pink color as a result of post-magmatic metasomatic processes. Muscovite granites containing muscovite in an amount from 1 to 15% are found in the contact zones of the Mokromoskovsky pluton. These rocks have the following mineral composition: oligoclase (35-40%), microcline (20-25%), quartz (30-35%), muscovite (1-15%), and biotite (0-4%).Materials and Methodology. The classification of pegmatite is based on field observation of pegmatite and description of 54 thin sections. The map was created with QGIS, and the diagram was created with MS Excel. Chemical analyses of granites (15 samples) and pegmatites (6 samples) were conducted at the Research Institute of Chemistry of V.N. Karazin Kharkiv University.Main Results. Biotite-bearing pegmatites. Zonal pegmatite veins are composed of biotite (30%), quartz (30%), microcline (15%), oligoclase (25%). The next zone is coarse-grained, composed of microcline (15%), oligoclase (15%), quartz (55%) and biotite (5%). The inner zone is composed of quartz and is not present in every zonal vein. Sometimes zonal pegmatites contain a zone of written granite. Azonal pegmatites are composed of coarse grains of oligoclase, microcline, quartz, and biotite. Muscovite-bearing pegmatites. Zonal veins include three zones: an outer zone of pegmatoid granite of muscovite-quartz-microcline composition; a subsequent zone of written granite; an inner zone of blocky pegmatite of quartz-microcline composition. Azonal pegmatites are composed of coarse grains of oligoclase, albite, microcline, quartz, and muscovite. The muscovite content reaches 30%.Conclusions. Two types of pegmatite veins have been identified - biotite-bearing and muscovite- bearing. Muscovite pegmatites occur in the southern, southeastern, and southwestern contact zone of the Mokromoskovsk pluton. Biotite pegmatites are encountered in the central part of the pluton. In the southern and southwestern contact zone, pegmatite veins are encountered in host rocks and form the Mokromoskovsky pegmatite field. Zonal and azonal pegmatite veins have been identified. Biotite-containing pegmatites consist of biotite, microcline, quartz, and oligoclase. Muscovite-containing ones contain muscovite, microcline, quartz, oligoclase, albite. Zonal and azonal pegmatite veins have been discovered; azonal veins intersect zonal veins. In the muscovite pegmatite veins of the Mokromoskovsky pegmatite field, high contents of tantalum, niobium, lithium, beryllium, rubidium, cesium, and sometimes rare earth metals have been discovered.